ADAPTASI MANAJEMEN PRODUK DALAM MENGHADAPI PASAR GLOBAL SEBAGAI STRATEGI PENINGKATAN DAYA SAING PERUSAHAAN - Lubis, Mhd. Ali Raja; Simbolon, Sahat Martua; Sihombing, Rian; Nugraha, Fahri Indra; Saragih, Lenti Susanna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Global market competition requires companies not only to produce high-quality products but also to adapt their product management strategies to the needs, preferences, and characteristics of consumers across different countries. In this context, product management adaptation becomes an important approach to maintaining business sustainability while enhancing corporate competitiveness amid the dynamic changes of the international market. This article aims to analyze the role of product management adaptation in responding to global market demands and to identify strategies that companies can implement to strengthen their competitive position. This study employs a literature review method by examining various scientific sources, including journals, books, and academic articles relevant to product management, global marketing, and corporate competitiveness. The findings indicate that product management adaptation can be carried out through adjustments in product design, quality, packaging, features, pricing, as well as distribution and promotional strategies according to the characteristics of target markets. Such adaptation contributes to increased customer satisfaction, broader market share, stronger brand image, and improved competitive advantage at the global level. In addition, this review highlights that the success of product management adaptation is influenced by a company’s ability to identify market trends, understand consumer culture, utilize digital technology, and integrate innovation into product development. Therefore, product management adaptation can be viewed as a strategic effort for companies to build sustainable competitiveness in the global market. Keywords: product management adaptation, global market, corporate competitiveness, marketing strategy, literature review